Fearless : imagine your life without fear - Lucado, Max. (Nashville, Tenn. : Thomas Nelson, 2009)
Texas pastor offers a faith-based primer on how to live without fear.
Why are we afraid? -- The villagers of Stiltsville : fear of not mattering -- God's ticked off at me : fear of disappointing God -- Woe, be gone : fear of running out -- My child is in danger : fear of not protecting my kids -- I'm sinking fast : fear of overwhelming challenges -- There's a dragon in my closet : fear of worst-case scenarios -- This brutal planet : fear of violence -- Make-believe money : fear of the coming winter -- Scared to death : fear of life's final moments -- Caffeinated life : fear of what's next -- The shadow of a doubt : fear that God is not real -- What if things get worse? : fear of global calamity -- The one healthy terror : fear of God getting out of my box -- Conclusion: William's Psalm.
Includes bibliographical references (pages 219-221).
Keywords: Fear -- Religious aspects -- Christianity